2013
DOI: 10.1111/phpp.12008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of systemic psoralen and ultraviolet A and narrowband ultraviolet B in treatment of chronic urticaria

Abstract: Both NB-UVB and PUVA show comparable efficacy in the treatment of chronic urticaria with minimal reversible side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…A study by Khefagy et al . confirmed that NB‐UVB and PUVA showed comparable efficacy in the treatment of CU with minimal side effects. Finally, a recent randomized prospective observer blinded study confirmed the efficacy of PUVA and NB‐UVB in steroid‐dependent CSU.…”
Section: Inducible Urticariassupporting
confidence: 58%
“…A study by Khefagy et al . confirmed that NB‐UVB and PUVA showed comparable efficacy in the treatment of CU with minimal side effects. Finally, a recent randomized prospective observer blinded study confirmed the efficacy of PUVA and NB‐UVB in steroid‐dependent CSU.…”
Section: Inducible Urticariassupporting
confidence: 58%
“…first reported improvement in CU following PUVA therapy in a patient who had co‐existing vitiligo and CU. A few subsequent studies reported a beneficial effect of different phototherapeutic modalities in the treatment of CU . Most of these studies are limited by small sample size and lack of definition of the baseline refractoriness of the disease.…”
Section: Discussionmentioning
confidence: 81%
“…Phototherapy has been found to be effective in the treatment of mastocytosis, dermographism and CU . The exact mechanism of action of phototherapy in urticaria is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the shortcomings of this study are the lack of a prespecified power calculation and inclusion of a control group, which would have enabled a more rigorous evaluation of the placebo‐deducted effect of phototherapy in CSU. To this end, the study provides no new knowledge compared with a previous smaller RCT, which also compared NB‐UVB with PUVA for CSU and to an RCT that evaluated NB‐UVB additionally to antihistamines in CSU . Also, a longer follow‐up time and an active comparison with one of the recommended drugs for CSU, such as omalizumab, would have been desirable.…”
mentioning
confidence: 98%